(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the development and application of Big Data technologies in foreign countries and their impact on economic growth, public administration, and corporate efficiency. The study highlights the extensive use of Big Data in the United States, Europe, and Asia across various sectors, including industry, finance, healthcare, transportation, and smart city systems. The paper also explores how leading global corporations such as Amazon, Google, Siemens, Alibaba, and Samsung leverage Big Data analytics to enhance competitiveness, optimize operations, and create innovative solutions.